Design of E-marketing Website as a Media for the Dissemination of Information and Product Marketing at PT. AJISAKA Semarang - Sulistyo, Michella Deninta; Jumi, Jumi -; Taviyastuti, Taviyastuti - (Politeknik Negeri Semarang, 2024)
Consumer lifestyle have been transformed by technology that provides online services for users to create networks where they can share and access information quickly. Real estate companies like PT. AJISAKA are required to adapt in the modern era to reach target audiences and promote their products by running digital marketing, one of which is with a web-based platform. The purposeof this research is to provide an e-marketing website as a medium for disseminating informationmand marketing product. The e-marketing website is expected to support the efficiency and effectiveness of the company”™s promotional activities. The method used in this research is System Development Life Cycle (SDLC) and built with Content Management System (CMS) WordPress. The result of this e-marketing website design is to create an infromation dissemination media platform that is easy to use to promote products that is user friendly and provides complete information. In addition, the e-marketing website is able to provide comfort for visitors because it can be accessed easily from a variety of devices